Pengaruh Marketing Mix Terhadap Minat Beli Pakaian Muslim di Butik Cordi Dalam Perspektif Islam - salma firdaus salma; Tiara Oktarienza; Vicky F Sanjaya (Universitas Ngudi Waluyo, 2022)
The purpose of this research is to find out the Marketing Mix at the Cordy boutique in Bandar Lampung on the buying interest of buyers from an Islamic perspective. This research uses quantitative methods, where the population used in this study is the customers of the cordy boutique in Bandar Lampung with a sample of 95 respondents. In this study, it is known that the results of the marketing mix affect buying interest. Mix has a significant effect on Buying Interest in Cordy Boutique fashion products. The real effect of Brand Image (X) on Purchase Interest (Y) can be shown by the value of R square = 0.263 or 26.3% while the remaining 72.7% is influenced by other factors not examined in this study.